2022
DOI: 10.3390/cells11071199
|View full text |Cite
|
Sign up to set email alerts
|

Global PIEZO1 Gain-of-Function Mutation Causes Cardiac Hypertrophy and Fibrosis in Mice

Abstract: PIEZO1 is a subunit of mechanically-activated, nonselective cation channels. Gain-of-function PIEZO1 mutations are associated with dehydrated hereditary stomatocytosis (DHS), a type of anaemia, due to abnormal red blood cell function. Here, we hypothesised additional effects on the heart. Consistent with this hypothesis, mice engineered to contain the M2241R mutation in PIEZO1 to mimic a DHS mutation had increased cardiac mass and interventricular septum thickness at 8–12 weeks of age, without altered cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Piezo1 has been found to play a critical role in the outflow tract and aortic valve development [ 124 , 125 ]. Since its expression had been shown to be present in both cardiomyocytes and cardiac fibroblasts [ 96 , 126 , 127 ], possible correlations between this channel and diseases of the cardiovascular system are a natural next focus for investigation. Table 1 summarizes the current literature, reviewed below, about Piezo1 dysfunctional regulation in cardiac cells (myocytes and fibroblasts) and our preliminary hypothesis about its beneficial targeting in fibroblasts.…”
Section: Piezo1 and The Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezo1 has been found to play a critical role in the outflow tract and aortic valve development [ 124 , 125 ]. Since its expression had been shown to be present in both cardiomyocytes and cardiac fibroblasts [ 96 , 126 , 127 ], possible correlations between this channel and diseases of the cardiovascular system are a natural next focus for investigation. Table 1 summarizes the current literature, reviewed below, about Piezo1 dysfunctional regulation in cardiac cells (myocytes and fibroblasts) and our preliminary hypothesis about its beneficial targeting in fibroblasts.…”
Section: Piezo1 and The Heartmentioning
confidence: 99%
“…Specifically, Piezo1 involvement in cardiac fibrosis was already taken into consideration by Fiona Bartoli et al in a very recent article [ 126 ]. Their work shows that a global gain-of-function Piezo1 mutation in mice is responsible for the amplificated calcium flow and both the overstimulated downstream p38 signaling and IL-6 secretion in cardiac fibroblasts.…”
Section: Piezo1 and The Heartmentioning
confidence: 99%
“…This is certainly the case for the hereditary xerocytosis where gain of function variants in PIEZO1 affect red blood cell physiology. Although, no data is available at present regarding the prevalence of cardiac arrhythmias in patients suffering from this condition, mice have been engineered to contain a specific gain of function PIEZO1 mutation found in these patients [22]. Interestingly, these animals develop cardiac hypertrophy and fibrosis, a problem primarily associated with dysfunctional fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…COL3A1 plays a pivotal role in the extracellular matrix. It has been reported that the abnormal expression of COL3A1 was closely associated with fibrosis in the cardiovascular system and spinal ligaments, indicating COL3A1’s capacity to maintain the functions of fibroblasts 39,40 . Rachel et al found that patients with vascular Ehlers‐Danlos syndrome, a genetic disease caused by the COL3A1 exon skipping mutations and presented with increased vascular fragility, suffered from systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%